The Style of Sufistic Interpretation: A Philological Study and Content Analysis of the Manuscripts By Three Popular Ulemas in West Kalimantan - Syarif Syarif (Al-Albab, 2020)
This paper aims to explain the content and inclination of the interpretive thoughts of the Sufi scholars in the Province of West Kalimantan. Among the Sufi scholars most popular in West Kalimantan in the 19th century and 20 were Ahmad Khatib al-Sambasi (1802-1879 AD), Muhammad Imran Basuni (1885-1953 AD) and Isma'il Mundu (1870-1957 AD). The works produced by these scholars are still in the form of manuncripts as the objects of study in this paper. This is a library research with philological and historical approaches. There are several stages in philological research including inventory, description of manuscripts, transfer of script and transfer of language. To support those four phases of philological research, the researcher employes content analysis in doing further exploration to the resermanuscripts. Very supprising, specific findings are presented. First, there are fifteen interpretations in the manuscript of Fathu Al-‘Arifin and eight in the Bidayatu Al-Tauhid Fi Ilmi Al-Tauhid. While in Mukhtasaru Al-Mannan Ala Aqidahti Al-Arahman, the contents of the interpretation are not found. Secondly, the patterns of interpretive thoughts used by Ahmad Khatib al-Sambasi and Muhammad Basuni bin Muhammad Imran contained in Fathu Al-‘Arifin and Bidayatu Al-Tauhid Fi Ilmi Al-Tauhid are of sufistic interpretation using the tahlili method. Whereas the thought pattern of Ismail Mundu's interpretation in Mukhtasaru Al-Mannan Ala Aqidahti Al-Arahman cannot be found. It is because the 20-pages manuscript consists of a summary that discusses the science of tawheed and Ismail Mundu did not quote any verses of the Qur'an in the manuscript.